Prevalence and prognostic impact of physical frailty in interstitial lung disease: A prospective cohort study. Issue 7 (19th April 2021) - Farooqi, Mohammed A. Malik; O'Hoski, Sachi; Goodwin, Sarah; Makhdami, Nima; Aziz, Afia; Cox, Gerard; Wald, Joshua; Ryerson, Christopher J.; Beauchamp, Marla K.; Hambly, Nathan; Kolb, Martin
Abstract: Background and objective: Physical frailty is associated with increased mortality and hospitalizations in older adults. We describe the prevalence of physical frailty and its prognostic impact in patients with a spectrum of fibrotic interstitial lung disease (ILD). Methods: Patients with fibrotic ILD at the McMaster University ILD programme were prospectively followed up from November 2015 to March 2020. Baseline data were used to classify patients as non‐frail (score = 0), pre‐frail (score = 1–2) or frail (score = 3–5) based on modified Fried physical frailty criteria. The association between physical frailty and mortality was assessed using time‐to‐event models, adjusted for age, sex, lung function and diagnosis using the ILD Gender–Age–Physiology (ILD‐GAP) score. Results: We included 463 patients (55% male, mean [SD] age 68 [11] years); 82 (18%) were non‐frail, 258 (56%) pre‐frail and 123 (26%) frail. The most common ILD diagnoses were idiopathic pulmonary fibrosis ( n = 183, 40%) and connective tissue disease‐associated‐ILD ( n = 79, 17%). Mean time since diagnosis was 2.7 ± 4.6 years. There were 56 deaths within the median follow‐up of 1.71 (interquartile range [IQR] 1.24, 2.31) years. Both frail and pre‐frail individuals had a higher risk of death compared to those categorized as non‐frail at baseline (adjusted hazard ratio [aHR] 4.14, 95% CI 1.27–13.5 for pre‐frail and aHR 4.41, 95% CI 1.29–15.1 for frail). Conclusion: Physical frailty is prevalent in patients with ILD and is independently associated with an increased risk of death. Assessment of physical frailty provides additional prognostic value to recognized risk scores such as the ILD‐GAP score, and may present a modifiable target for intervention. Abstract : Physical frailty is common in interstitial lung disease (ILD) and is independently associated with increased death after adjusting for age, sex lung function and ILD diagnosis. It represents a potentially modifiable risk factor for mortality that should be assessed in patients with fibrotic ILD.